Enhancing host biochemical defence system against Bipolaris maydis through seed priming with maize (Zea mays) phyllosphere endophytic bacteria - PATTANAYAK, SUDEEPTA; GOGOI, ROBIN; KUMAR, AUNDY; BASHYAL, BISHNU MAYA; MANDAL, PRANAB KUMAR (The Indian Journal of Agricultural Sciences, 2025)
Maize (Zea mays L.) is an important cereal crop, significantly contributing to the global economy and advancing plant genetic research. One of the most serious diseases, maydis leaf blight (MLB), incited by Bipolaris maydis, reduces the yield and quality of maize. The present study was carried out during rainy (kharif) season (June–Oct) of 2022 and 2023 at ICAR-Indian Agriculture Research Institute, New Delhi to identify promising phyllosphere endophytic bacteria against Bipolaris maydis as an appropriate alternative to the traditional commercial fungicides, which also aligns with the goal of promoting sustainable and eco-friendly agriculture. Three different concentrations of phyllosphere endophytic bacteria, viz. Stentrophomonas maltophilia, Brevundimonas olei and Pseudomonas aeruginosa were investigated for MLB disease reduction and activation of maize biochemical defence system against Bipolaris maydis after seed priming. The recorded in planta percent disease index (PDI) data were analysed using a randomized block design (RBD) while all replications for biochemical assay were arranged in a completely randomized design (CRD) and subjected to the analysis of variance (ANOVA). Disease scoring in both seasons recorded the lowest PDI at the highest concentration of Stentrophomonas maltophila, followed by Brevundimonas olei and Pseudomonas aeruginosa. Biochemical activities of phenylalanine ammonia-lyase (PAL), PR protein β-1,3- glucanase, and non-enzymatic antioxidant including total polyphenol with total sugar content were recorded for both inoculated and uninoculated set of treatments. In addition, seeds primed with the highest concentration 1.0 at OD600 of Stentrophomonas maltophilia and Brevundimonas olei recorded elevated sugar levels, enzymatic as well as non- enzymatic activities after Bipolaris maydis inoculation. This study demonstrated that the changes in biochemical activities correspond with the developmental stages of the pathogen Bipolaris maydis which inhibited its growth. The biochemical defence activities varied differentially during disease progression on the host plant.